Citizens' Environmental Study Committee Meeting Briefing Report - Jane Tolmach::::::; Robert Brown:::::: (1970)
A memorandum informing city council of the impact of a proposed airport in the former Oxnard Air Base. Includes an introduction to the proposed noise standard for California airports.